Evidences for the depletion region induced by the polarization of ferroelectric semiconductors - Yuan, Guoliang (2011)
Ferroelectric materials possess spontaneous polarization pointing from negative to positive bound surface charges. When a ferroelectric semiconductor is polarized, the induced electric field can drive free carriers, e.g., electrons in an n-type material, to neutralize surface charges until such field becomes zero. Such diffusion of free carriers induces a depletion region. Polarization switch can move the depletion region to the opposite surface, thus it can be used to manipulate any properties that are affected by such depletion region, such as unidirectional current and photovoltaic current.